Research on low-rate DDoS attack of SDN network in cloud environment - Xingshu CHEN; Qiang HUA; Yitong WANG; Long GE; Yi ZHU (Tongxin xuebao)
Aiming at the problems of low-rate DDoS attack detection accuracy in cloud SDN network and the lack of unified framework for data plane and control plane low-rate DDoS attack detection and defense,a unified framework for low-rate DDoS attack detection was proposed.First of all,the validity of the data plane DDoS attacks in low rate was analyzed,on the basis of combining with low-rate of DDoS attacks in the aspect of communications,frequency characteristics,extract the mean value,maximum value,deviation degree and average deviation,survival time of ten dimensions characteristics of five aspects,to achieve the low-rate of DDoS attack detection based on bayesian networks,issued by the controller after the relevant strategies to block the attack flow.Finally,in OpenStack cloud environment,the detection rate of low-rate DDoS attack reaches 99.3% and the CPU occupation rate is 9.04%.It can effectively detect and defend low-rate DDoS attacks.